2005
DOI: 10.1136/jmg.2005.031377
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium fine mapping and haplotype association analysis of the tau gene in progressive supranuclear palsy and corticobasal degeneration

Abstract: Background: The haplotype H1 of the tau gene, MAPT, is highly associated with progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD). Objective: To investigate the pathogenic basis of this association. Methods: Detailed linkage disequilibrium and common haplotype structure of MAPT were examined in 27 CEPH trios using validated HapMap genotype data for 24 single nucleotide polymorphisms (SNPs) spanning MAPT. Results: Multiple variants of the H1 haplotype were resolved, reflecting a far greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
271
3
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(286 citation statements)
references
References 38 publications
(57 reference statements)
7
271
3
2
Order By: Relevance
“…In particular, the strong increase in aggregation propensity associated with the fourth microtubule binding repeat more than compensates for the depletion of 1N isoforms in AD (56). In contrast, haplotype H2, which is protective against PSP (7,8), supports increased inclusion of exon 3 as well as decreased inclusion of exon 10 relative to H1 (47,55). Moreover, levels of 2N forms of Tau are depressed in the Tau aggregates that accumulate in PSP (58 -60).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In particular, the strong increase in aggregation propensity associated with the fourth microtubule binding repeat more than compensates for the depletion of 1N isoforms in AD (56). In contrast, haplotype H2, which is protective against PSP (7,8), supports increased inclusion of exon 3 as well as decreased inclusion of exon 10 relative to H1 (47,55). Moreover, levels of 2N forms of Tau are depressed in the Tau aggregates that accumulate in PSP (58 -60).…”
Section: Discussionmentioning
confidence: 92%
“…Despite this canonical expression pattern, the six central nervous system Tau isoforms vary in relative amounts depending on both cis and trans gene regulatory mechanisms. The MAPT haplotype, for example, influences levels of both exon 3 and exon 10 containing transcripts, with the H1 haplotypes that favor inclusion of exon 10 being associated with the corticobasal degeneration and PSP forms of FTLD (6 -8), and the H2 haplotype that favors exon 3 inclusion being protective against PSP (7,8). Exon 10 inclusion also is modulated by certain intronic point mutations, with those that increase exon 10 containing transcripts, causing familial forms of FTLD (9,10).…”
mentioning
confidence: 99%
“…11 These two clades can be delineated via the a 238 bp insertion/deletion polymorphism within intron 9 (del-In9). 10,12,13 Association studies of H1 versus H2, in AD have to date produced largely negative findings. [13][14][15][16] Recent studies have reported that whereas the H2 haplotype is in fact a single nonrecombining haplotype, the more common H1 haplotype is more diverse, showing typical linkage disequilibrium (LD), although not with H2.…”
Section: Introductionmentioning
confidence: 99%
“…In our quest to investigate the functional basis of the risk conferred by the MAPT H1 haplotype with PSP and CBD, we identified, H1c, a sub-haplotype of H1 that drives this risk and therefore probably contains polymorphism(s) that have a functional effect on MAPT gene function [5,12] Our work however, implicates the MAPT promoter and the rs242557 SNP in particular and we have failed to identify any H1c-specific SNPs that would explain the effects on splicing of exon 10 to produce elevated levels of exon 10+ mRNA coding for the four-repeat tau (4R-tau) in particular [12]. Separate work by Rademakers et al [24] and also the conditional analysis in the recent PSP GWAS [9] Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…with risk of neurodegeneration, we analysed the underlying MAPT genetic variation in PSP and CBD cases and showed that H1c, a sub-haplotype of the H1 clade, drives the association of the H1 haplotype -in other words, the H1c sub-haplotype contains the functional polymorphism that modulates risk [5,6]. We also showed that the H1c sub-haplotype is associated with Alzheimer's disease (AD) [7].…”
Section: Introductionmentioning
confidence: 98%